Beneficial effects of Brassica juncea on cognitive functions in rats - Thakur A.K.; Chatterjee S.S.; Kumar V. (My University, 2025)
Context. Brassica juncea (BJ; Linnaeus) Czern & Coss (Brassicaceae), commonly known as Indian mustard, are enriched in redox-active polyphenols with antidiabetic activities. Diverse other health benefits of this edible plant have been described in classical Ayurvedic texts. Objective: The reported experiments were designed to assess therapeutic potential of a methanol extract of BJ leaves for treatment of cognitive disorders associated with diabetes or caused by central cholinergic dysfunctions. Materials and methods: Elevated plus-maze and active- and passive-avoidance tests were used to assess anti-amnesic potentials of BJ (100, 200 and 400 mg/kg/day, p.o., for 10 days) in alloxan diabetic or scopolamine-challenged rats. Treatment effects on brain acetylcholinesterase (AChE), superoxide dismutase (SOD) and catalase (CAT) activities were quantified in behavioral tested animals. Results: Anti-amnesic efficacy of all three tested BJ doses against scopolamine-induced amnesia was almost equal in all behavioral tests. Such efficacy of the extract in diabetic rats was increased always with its increasing doses. All treatments of BJ dose dependently decreased the elevated level of AChE, and significantly increased the SOD and CAT levels in brain homogenates of scopolamine-challenged and diabetic rats. Minimal effective oral daily doses of BJ in all tests were 100 mg/kg/day for 10 consecutive days. Discussion and conclusion: Our observation indicates that BJ could be a therapeutic option for treatment of cognitive disorders associated with diabetes, or caused by cholinergic deficit and brain oxidative status. They also indicate that the bioactive constituents or mode of actions involved in observed effects of the extract in scopolamine-challenged or diabetic rats are most probably not the same. © 2013 Informa Healthcare USA, Inc. All rights reserved.